EXPLORING PERCEPTIONS OF EMPLOYERS ON COMMUNICATION SKILLS AMONG FRESH GRADUATES (Practitioner Research, 2019)
Every employer wants their newly hired employees to possess vital employability skills that can enhance the performance and growth of their organisations. Employers rely on universities to provide university graduates to have been trained adequately before entering the workforce. Adequate employability skills possessed by prospective employees will certainly satisfy employers’ expectations. In the competitive 21st century, one tangible soft skill deems essential is communication skills. They prefer graduates who possess great soft and communication skills that can enhance their organisations’ growth and performance. Effective communication is considered one of the vital skills that most employers look for in their potential new employees to possess. How marketable graduates (prospective employees) is and how soon they could be hired successfully depends on the types of programmes, tasks and activities and skills they have acquired during their university years. This exploratory research paper reports findings based on the employers’ perceptions towards graduates whom they hired in their organisations. Date obtained from interviews with 3 employers from private company, semi-government and government bodies indicate some concern over the kind and the amount of communication skills our fresh graduates possess and exhibit. From these 3 employers, it was discovered that most fresh graduates lack negotiation skills and proper communication skills which include presentation skills and interviewing. Most fresh graduates lack certain social communication skills such as not being diplomatic. These employers suggest the needs for fresh graduates to be trained in authentic situations by giving them real life simulations. The training programmes designed need to allow them to showcase and display their abilities and skills from the various learning activities taught in Malaysian universities and at the same time encourage many community service responsibility (CSR) activities to inculcate not only problem-solving skills but also communication skills. It is also suggested that universities need to keep upgrading their communication programmes in order to produce employable graduates with better chances of being hired successfully by work markets.